2014
DOI: 10.1016/j.celrep.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring AMPK and Mitochondrial Retrograde Signaling for Metabolic Control of Aging and Histone Acetylation in Respiratory-Defective Cells

Abstract: Abnormal respiratory metabolism plays a role in numerous human disorders. We find that regulation of overall histone acetylation is perturbed in respiratory-incompetent (ρ(0)) yeast. Because histone acetylation is highly sensitive to acetyl-coenzyme A (acetyl-CoA) availability, we sought interventions that suppress this ρ(0) phenotype through reprogramming metabolism. Nutritional intervention studies led to the discovery that genetic coactivation of the mitochondrion-to-nucleus retrograde (RTG) response and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 53 publications
2
28
0
2
Order By: Relevance
“…It was recently reported that Snf1 is required to overcome the impaired respiratory function caused by loss of mitochondrial DNA in stationary phase[32]. Our findings complement this notion, indicating that lack of Snf1 causes an increase of cellular dependence of mitochondrial function.The common feature of the phenotypes described for snf1Δ cells in this paper is that they are almost undetectable when cells grow in the presence of 5% glucose.…”
supporting
confidence: 92%
“…It was recently reported that Snf1 is required to overcome the impaired respiratory function caused by loss of mitochondrial DNA in stationary phase[32]. Our findings complement this notion, indicating that lack of Snf1 causes an increase of cellular dependence of mitochondrial function.The common feature of the phenotypes described for snf1Δ cells in this paper is that they are almost undetectable when cells grow in the presence of 5% glucose.…”
supporting
confidence: 92%
“…In a situation of mitochondrial dysfunction, ERCs formation increase by modifications of metabolism of the glutamate pathway (Friis et al 2014). Subsequent studies have shown that CR extends RLS by increasing respiratory activity (Lin et al 2002).…”
Section: Replicative Longevity and Mitochondriamentioning
confidence: 99%
“…It is not clear if this ratio of nucleocytosolic and mitochondrial acetyl-CoA is maintained as cells progress through the diauxic shift into stationary phase and whether there is a cross talk mechanism coordinating and regulating the levels of acetylCoA in both compartments. However, mitochondrial metabolism is required to maintain cellular levels of acetyl-CoA and histone acetylation in stationary phase; interestingly, this requirement is bypassed by simultaneous activation of the SNF1 and retrograde pathways (107). This bypass upregulates synthesis of the storage carbohydrate trehalose, which is subsequently metabolized to provide acetyl-CoA (107).…”
Section: Regulation Of Acetyl-coa Homeostasismentioning
confidence: 99%